ChemInform Abstract: Organocatalytic Stereoselective Addition of Aldehydes to Acylquinolinium Ions. Issue 46 (October 2016) - Mengozzi, Luca; Gualandi, Andrea; Cozzi, Pier Giorgio
Abstract: A direct and simple activation of quinolines, without isolating unstable intermediates, or using isolated N, O‐acetals in the presence of Lewis or Broensted acids, is described.